Nonclassical austenite-martensite interfaces - Ball, J; Carstensen, C (1997)
In the last 10 years a new theory of martensitic transformations based on nonlinear elasticity has been developed and intensively studied by J.M. Ball and R.D. James and others. Microstructures are understood in the theory as minimizing sequences for the total free energy, and are conveniently described using Young measures.For the case of the classical austenite-martensite interface, in which a pure phase of austensite meets a simple laminate of martensite, the formulae of the crystallographic theory of martensite for the orientation of the habit plane are recovered from the energy-minimization picture.The theory leads naturally to the prediction of more complex austenite-martensite interfaces, in which a pure phase of austenite meets a more complicated microstructure of martensite. The possible interfaces are computed in case that the martensite wells correspond to an orthorombic to monoclinic lattice transformation. Besides the classical interfaces, with simple laminate of martensite, new possible interfaces are presented which correspond for a larger set of lattice parameters. Then, for certain parameters, it can be concluded from the theory that possible interfaces are planes.